LEGAL FORMALISM VS SOCIAL-RELIGIOUS REALITY: A PROGRESSIVE LEGAL ANALYSIS OF CRIMINAL PENALTIES FOR UNREGISTERED MARRIAGES UNDER THE 2023 NATIONAL CRIMINAL CODE - Alfi Karomah; M. Firza Rausyan Fikri; M. Syukron Jazil; Miftahus Sholehudin (Makkah: Journal Of Islamic Studies, 2026)
This research examines Article 412 of Law No. 1 of 2023 on the National Criminal Code from a progressive legal perspective concerning the practice of nikah siri in Indonesia. The persistence of nikah siri within Muslim communities reflects a tension between the state’s legal formalism, which requires marriage registration, and the socio-religious reality that considers marriage valid once religious pillars and requirements are fulfilled. This research aims to analyze the normative construction of Article 412 of the National Criminal Code toward unregistered marriage couples and to examine the conflict between formal law and social reality. The research employs a normative juridical method using statutory and conceptual approaches based on Satjipto Rahardjo’s progressive legal theory. The findings reveal that Article 412 has the potential to criminalize couples in nikah siri marriages because state law does not clearly distinguish between cohabitation and marriages that are religiously valid but administratively unregistered. Such criminalization reflects an overly formalistic legal approach that fails to address the root causes of the issue, including limited access to marriage registration, economic constraints, and the strong socio-religious legitimacy of nikah siri. Therefore, a more humane and substantively just legal policy reform is required through strengthening marriage validation mechanisms (isbat nikah), expanding access to marriage registration, and providing stronger legal protection for women and children.